Sovereign debt restructuring and debt sustainability : an analysis of recent cross-country experience - Finger, Harald (IMF WashingtonUS, 2007)
Focuses on debt restructuring operations and assesses whether debt sustainability was restored. Looks at debt owed to private creditors and reviews the experiences of the past several years during which a number of countries have restructured their sovereign debt in the context of efforts to resolve a crisis.